Dual-channel NIR activatable theranostic prodrug for in vivo spatiotemporal tracking thiol-triggered chemotherapy - Ye, Mingzhou (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Real-time tracking for where (W), when (W), and how (H) prodrugs are delivered and activated in vivo is a great challenge for prodrug development. Disulfide linkage-based prodrugs as well as their delivery systems have been studied extensively, but the WWH question in spatial and temporal (spatiotemporal) precision remains unanswered. Herein, we present a novel prodrug of camptothecin (CPT) linked to a near-infrared (NIR) cyanine dye via a disulfide linkage (Cy-S-CPT). The cleavage of the disulfide bond in Cy-S-CPT by endogenous glutathione (GSH) can activate the anti-cancer drug CPT and induce a remarkable fluorescence shift from 825 to 650 nm, thereby providing dual fluorescent channels to real-time track the prodrug biodistribution and activation in vivo. Impressively, the dual-channel NIR fluorescence bioimaging exhibits the pervasive drug distribution, i.e., the biodistribution of the intact prodrug was traced at the 825 nm-NIR fluorescence channel, whereas the activated drug was tracked at the 650 nm red fluorescence channel. In this way, we can overcome the blind spot in the metabolism kinetics of prodrugs in a certain organ or tissue. As demonstrated, the prodrug prompts activation in all the organs, particularly in the liver after an intravenous injection, and achieves predominant accumulation and activation in tumors at 24 h post injection. Cy-S-CPT loaded in PEG–PLA nanoparticles display significantly improved therapeutic efficacy and low side effects with respect to the clinical used drug CPT-11. As a consequence, the NIR spatiotemporal bioimaging in vivo with dual fluorescence channels allows the prodrug release profile to be extracted precisely, particularly in visualizing drug-released information from complex biological systems such as mice, thereby providing a unique opportunity to take insight into the relationship between theranosis and pharmacokinetics.